Sacrificing the Break: Exploring Intrinsic and Extrinsic Motivation Among EFL Summer Class Students - Engelina Salainti; Alan Hubert Frederick Sanger (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
Intensive summer language courses offer an accelerated path for academic progression, yet they require substantial temporal sacrifices from students who must study during their official holidays. This study investigated the learning motivation dynamics and psychological experiences of EFL students navigating a high-density, daily summer English program at an Indonesian university. Employing a qualitative descriptive case study design, data were gathered through individual, one-on-one semi-structured interviews with five purposively selected university students (n = 5). The individual interview records were compiled into complete verbatim transcripts and analyzed using a descriptive narrative approach. The findings revealed that although students experienced initial emotional friction, including laziness, nervousness, and social media jealousy, they successfully maintained their learning focus. Their academic endurance was heavily driven by clear extrinsic goals, such as securing grades, finishing credit requirements, and ensuring timely graduation. Furthermore, a supportive classroom environment, highly interactive teaching styles, and smaller class sizes effectively transformed the potential stress of a fast-paced schedule into a positive tool for focused learning. This study implies that the success of intensive programs relies heavily on instructors maintaining empathetic, high-engagement pedagogy to mitigate student mental fatigue.